Speckle Tracking Echocardiography to Evaluate for Pulmonary Hypertension in Chronic Obstructive Pulmonary Disease. (2nd September 2016) - Rice, Jessica L.; Stream, Amanda R.; Fox, Daniel L.; Geraci, Mark W.; Vandivier, R. William; Dorosz, Jennifer L.; Bull, Todd M.
Abstract: Pulmonary hypertension (PH) is a common complication of chronic obstructive pulmonary disease (COPD), increasing morbidity and mortality. Current echocardiographic measures have poor predictive value for the diagnosis of PH in COPD. Right ventricular (RV) strain obtained by speckle tracking echocardiography (STE) is a measure of myocardial deformation which correlates with RV function and survival in subjects with pulmonary arterial hypertension. We hypothesized that RV strain measurements would be feasible and correlate with invasive hemodynamic measurements in patients with COPD. Retrospective analysis of RV strain values from subjects with severe COPD with echocardiogram within 48 hours of right heart catheterization was performed. First, 54 subjects were included in the analysis. Right ventricular systolic pressure (RVSP) and RV strain could be estimated in 31% and 57%, respectively. Then, 61% had RV-focused apical views, and of those, RV strain could be obtained for 94%. RV free wall strain correlated with PVR (r = 0.41, p = 0.02). Subjects with pulmonary vascular resistance (PVR) > 3 Wood units (WU) had less negative (worse) RV free wall strain values than those with PVR ≤ 3 WU, with a median strain of −20 (−23, −12) versus −23 (−29, −15), p < 0.05. A receiver operating characteristic curve demonstrated an RV free wall strain of > −23 to be 92% sensitive and 44% specific for identifying PVR > 3 WU (AUC 0.71). RV strain estimates are feasible in the majority of subjects with severe COPD. RV strain correlates with PVR and may improve screening for PH in subjects with COPD.